2022
DOI: 10.21272/fmir.6(4).101-118.2022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dividend Policy on Share Price Movement: Focusing on Companies Listed on the Nigerian Stock Exchange Market

Abstract: This study examined the relationship between dividend policy and share price movements with evidence from firms listed on the Nigerian Stock Exchange. A systemization literary approach for data analysis was panel regression analysis and Generalized Methods of Moments (GMM). Panel data covering the year 2011-2020 were obtained from the financial statements of twenty firms listed on the Nigerian stock exchange. It was discovered that dividend yield has negative relationship with share price movement. It was disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Total and direct effects of dividend yield have a negative and significant influence on a share price that indicates low or (high) dividend yield negatively impacts high or (low) share price. The result was comparable to earlier studies' outcomes of Allen and Rachim (2014), Singh and Tandon (2019), and Kayode et al (2022). The result revealed an insignificant and negative indirect effect of dividend yield on share price through return on assets (b1 = -0.0396, t = -1.03).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Total and direct effects of dividend yield have a negative and significant influence on a share price that indicates low or (high) dividend yield negatively impacts high or (low) share price. The result was comparable to earlier studies' outcomes of Allen and Rachim (2014), Singh and Tandon (2019), and Kayode et al (2022). The result revealed an insignificant and negative indirect effect of dividend yield on share price through return on assets (b1 = -0.0396, t = -1.03).…”
Section: Resultssupporting
confidence: 87%
“…However, retention ratio has little impact on stock prices. A statistically significant correlation exists between dividend yield and stock price volatility and a negative correlation between share price movement and business size (Kayode et al, 2022). dividend yield, dividend payout ratio, and firm size also affect share price volatility.…”
Section: Empirical Studiesmentioning
confidence: 92%
“…Previous research conducted by (Septyadi & Bwarleling, 2020), (Marini & Sutrisna Dewi, 2019), (Dewi & Paramitha, 2019) (Zainudin et al, 2018, (Sugathadasa, 2018), (Nurleli & Wibisono, 2021), (Akram Ahmad et al, 2018), (Hieu Nguyen et al, 2020), (Khan, 2019), (Kayode I. et al, 2022), (Singh & Tandon, 2019), (Fiorenza et al, 2023), (Hossin & Ahmed, 2020), which states that dividend payments negatively affect stock price volatility. A high Dividend Payout Ratio (DPR) indicates the company has strong cash flow and is able to pay high dividends.…”
Section: Introductionmentioning
confidence: 92%
“…In Nigeria, Kayode et al (2022) observed that dividend yield negatively and significantly influences share price movement, while the influence of firms' size is positive and significant on stock price volatility. In Nigeria, Emeka and Onyeogubalu (2021) showed that dividend payout, dividend yield and dividend per share significantly and positively influence firms' share price.…”
Section: Dividend Per Share and Market Price Per Sharementioning
confidence: 99%